Optimizing Decision Making in Manufacturing: An Analysis of the Effectiveness of a DSS Using the Weighted Product Method - I Gede Iwan Sudipa; Endang Setyawati; Fajriana Fajriana; Jimmy Moedjahedy; Robbi Rahim; Iwan Adicandra (JINAV: Journal of Information and Visualization, 2022)
This study aimed to evaluate the effectiveness of a DSS utilizing the WP method in improving the decision-making process and overall performance of a manufacturing company. The study collected data over a six-month period and found that the use of the DSS resulted in a 5% reduction in production costs, a 40% increase in market demand, and a 40% increase in profit. Additionally, user satisfaction level with the DSS improved by 33%. Regression analysis was conducted to determine the relationship between the use of the DSS and the performance of the company, the results showed that there was a statistically significant relationship between the use of the DSS and the reduction in production costs, increase in market demand, and increase in profit. Additionally, the analysis showed that the satisfaction level of the users of the system also significantly improved. The results of this study provide evidence that the use of a DSS with the WP method can be an effective tool for improving the decision-making process and overall performance of a manufacturing company. The study suggests that the DSS can be an effective tool for improving the performance of the company. However, it's important to note that the results of this study are specific to the manufacturing company, and may not generalize to other types of companies or industries.